YIELD OF ABRAMS NEEDLE PLEURAL BIOPSY IN EXUDATIVE PLEURAL EFFUSION - ullah, Ihsan; Khan, Nisar; Jadoon, Huma; Zaman, Munawar; Ahmed, Ashfaq (Journal of Ayub Medical College Abbottabad, 2009)
Background: Pleural effusion is the abnormal collection of fluid in the pleural space resulting from excessive fluid production or decreased absorption and it is one of the most common clinical conditions that we come across in pulmonology clinics and in hospitals. The objective of prospective study was to evaluate the diagnostic role of Abrams Needle Biopsy in Exudative Pleural Effusion Methods: The study was performed at the Department of Pulmonology, Ayub Teaching Hospital, Abbottabad over a period of 1 year, i.e., January 2008 to December 2008. Sixty-three patients of either sex and all ages with exudative pleural effusion, on whom Abrams Needle Biopsy was performed were included in the study. Minimum of four specimens from each patient were taken and histopathology done. Results: Out of 63 patients, histopathology revealed the cause in 60 (95%) cases. Tuberculosis, malignancy and rheumatoid pleurisy were confirmed in 34, 24, and 2 cases respectively. Specimens of 3 patients did not reveal any result and showed non-specific inflammation and were further investigated accordingly. Conclusion: The diagnostic yield of Biopsy was 95%. Pleural biopsy is still a reliable and valuable investigation in diagnosing pleural effusion, provided that adequate pleural specimen is taken. Keywords: Pleural biopsy, Exudative pleural effusion, malignant pleural effusion, Tuberculosis